2007
DOI: 10.1007/s11207-007-9051-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Near-Solar Plasma Turbulence Parameters Using the Radio Sounding Technique at Small Heliocentric Distances

Abstract: We investigate the temporal correlation function and the mean intensity of monochromatic radio emission in the neighborhood of a regular caustic produced by radio sounding of near-solar plasma. Using asymptotic analysis and numerical simulation, we determine conditions under which the temporal correlation function is related to the temporal structure function by a relation similar to that used for the solar wind diagnostics Harmon, Astrophys. J. 337, 1023, 1989) in the case of weak refraction of radio waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Here unless otherwise specified, the outer scale, the spectral exponent, and the solar wind velocity are set as l o = 2 × 10 7 m, p = 11/3, and V = 300 km/s, respectively. This is a compromise between those assumed by Ho et al [] and Thejappa and MacDowall [] and the experimental results reported by Afanasiev and Afanasiev []. Notably, even though the outer scale may vary with radial direction (and there are some well‐studied spectral exponents that are much flatter), we only use the average outer scale value and the extensively used Kolmogorov spectrum.…”
Section: Numerical Simulations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here unless otherwise specified, the outer scale, the spectral exponent, and the solar wind velocity are set as l o = 2 × 10 7 m, p = 11/3, and V = 300 km/s, respectively. This is a compromise between those assumed by Ho et al [] and Thejappa and MacDowall [] and the experimental results reported by Afanasiev and Afanasiev []. Notably, even though the outer scale may vary with radial direction (and there are some well‐studied spectral exponents that are much flatter), we only use the average outer scale value and the extensively used Kolmogorov spectrum.…”
Section: Numerical Simulations and Discussionmentioning
confidence: 99%
“…Link performance near the Sun can be improved by operating at high frequencies, using optical communications, or relay communication [ Brandl et al , ]; but it is possible to optimize a properly linked margin design given an estimate of the amplitude fluctuations [ Basu et al , ] and this should be done in any case. In addition, an analytical model of the amplitude fluctuations would help invert observations of the amplitude fluctuations to improve our knowledge of the physical processes in the solar corona [ Afanasiev and Afanasiev , ; Crawford , ; Yakovlev , ]. The principal objective of this paper is to present an improved model of the amplitude fluctuations and an analytical solution for the scintillation index in weak scattering.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we restrict the heliocentric distance in the range of 2R su n to 4R su n . Therefore, we use the following solar wind density model, which has a high accuracy when 2R su n < r < 20R su n [23].…”
Section: Generalized Refractive Index Fluctuation Spectrum For the Nomentioning
confidence: 99%